Development and characterization of peptide antioxidants from sorghum proteins - Xu, Shiwei (Kansas State University, 2018)
Antioxidants are widely used in food industries to delay lipid oxidation and prevent oxidative deterioration. In recent years, growing interests in developing safe and efficient antioxidants from natural sources due to the health-related risks associated with synthetic antioxidants. Recently, peptide antioxidants have drawn growing interests as since proteins are a macronutrient with various functionalities and high consumer acceptability. A lot of dietary proteins have been validated for their antioxidant potentials especially those obtained from animal proteins, nuts and pulses. Relatively less information is available on characterizing the antioxidant profile of cereal protein, and even less for sorghum protein. Sorghum is the fifth largest crop worldwide and is the third in United States. U.S. is leading in global sorghum production and distribution, and the state of Kansas is producing nearly half of U.S. sorghum. Currently, about one third of the U.S. sorghum is being used for ethanol production, resulting in more than 450 kilotons of by-products (e.g., DDGS) annually, which were often discarded or underutilized. DDGS is a premium protein source (~ 30% protein) that could be potentially modified into value-added products such as peptide antioxidants. In this study, relevant literatures detailing the extraction of cereal proteins, enzymatic hydrolysis of proteins, purification and characterization of hydrolysates, and evaluation of antioxidant profiles were extensively reviewed in Chapter 1. As preliminary experiments, sorghum kafirin protein was extracted from defatted sorghum white flour and hydrolyzed by 10 different types of enzymes from microbial, plant and animal sources. Hydrolysates prepared with Neutrase, Alcalase, and Papain displayed the most promising antioxidant activities as well as total protein recovery were primarily selected and investigated in depth described in Chapter 2, Chapter 3, and Chapter 4. The reaction conditions including substrate content, enzyme-to-substrate ratio, and hydrolysis time are critical parameters in producing peptides with desired activity and consistency, were therefore examined and optimized for each case of kafirin hydrolysates. The antioxidant capacity of the resulting hydrolysates was measured for antioxidant capacity through in vitro assays (DPPH, ABTS, ORAC, reducing power, and metal chelating) and then demonstrated in model systems (oil-in-water emulsion and ground meat). The fractions of hydrolysates possessing strongest activities were further fractionated by gel filtration and HPLC. Peaks representing the largest areas from HPLC were identified for major sequences by MALDI-TOF-MS. The experiment results indicated that all the three selected fractions of kafirin hydrolysates revealed excellent inhibition effects against oil and fat oxidations, which could be employed as tools to predict their performances in real food products. In addition, the structure studies showed that medium-sized hydrolysates of Neutrase (3 – 10 kDa) and Alcalase (5 – 10 kDa), and small-sized hydrolysates of Papain (1 – 3 kDa) exhibited relatively stronger activities. This study provided a workable processing method and critical reaction parameters for the production of peptide antioxidants from sorghum protein. The experiment results revealed that the sorghum peptide antioxidant could act through multiple mechanisms including free radical scavenging, metal ion chelation, hydrogen donating, and forming physical barriers to minimize the contact of oxidative agents to targets. These antioxidative peptides are a promising ingredient that can be potentially incorporated to food and feed products as alternatives to synthetic antioxidants or synergetic elements to nonpeptic antioxidants for protection of susceptible food ingredients. This study also made a positive impact to sorghum ethanol industry by guiding the conversion of sorghum protein-rich by-products into value-added antioxidant products as an additional revenue stream.
Keywords: Peptide antioxidant; Sorghum; Bioactive peptide; Protein; Enzymatic hydrolysis; Natural antioxidants